PERANCANGAN SISTEM INFORMASI APLIKASI PENCARIAN STASIUN KRL JABODETABEK TERDEKAT BERBASIS ANDROID - Betesda Betesda (JURNAL MITRA MANAJEMEN, 2020)
Abstract- Transportation has been long part of people life, especially for the urban. The transportation need not only applied for the local, Jakarta as a capital city must be full of foreigner either for business purpose or others, and they are need a public transportation as well. Commuter Line Jabodetabek is the most preferable public transportation to avoid Jakarta’s traffic. The idea is to create a mobile application system which could easily help Commuter Line Jabodetabek user to get the information about the existence of the nearest station. The application system is analyzed and designed with a mobile application development approach. Application developed with JAVA, IDE (Integrated Development Environment) used is Android Studio, and to determine the nearest distance using Google Maps API. This application is equipped with mileage information and detailed station information so that station seekers can easily and accurately determine the nearest station and route to the station. Keywords: Commuter Line Jabodetabek, Train Station, JAVA, Android Studio.